2000
DOI: 10.1001/archfami.9.10.1028
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Severity and Perceptions in Subjects With Panic Attacks

Abstract: Subjects with panic attacks perceive symptoms as more embarrassing than controls, and have different perceptions about particular symptoms. Cognitive approaches addressing negative patient perceptions may reduce anxiety, inappropriate use of health care services, and adverse outcomes. Arch Fam Med. 2000;9:1028-1035

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Chest pain is a common symptom in community-based patients with panic disorder and is included in the definitional criteria for panic disorder. 16 Table 1 7,9,17-38 presents the prevalence of panic disorder in patients with chest pain. The prevalence of panic attacks, which fail to meet the criteria for panic disorder, is just as high.…”
Section: Chest Pain and Panic Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Chest pain is a common symptom in community-based patients with panic disorder and is included in the definitional criteria for panic disorder. 16 Table 1 7,9,17-38 presents the prevalence of panic disorder in patients with chest pain. The prevalence of panic attacks, which fail to meet the criteria for panic disorder, is just as high.…”
Section: Chest Pain and Panic Disordermentioning
confidence: 99%
“…Patients with panic disorder are emotionally sensitive. 16 As a group, those with panic attacks are more concerned about pain, are more convinced that they have a disease, and are more phobic about disease and death than control subjects. 73 Those with fear as part of their attacks have more panic symptoms with a more recent onset.…”
Section: Characteristics Of Chest Pain In Panic Disordermentioning
confidence: 99%
“…Indeed, cognitive psychology proposes that biases towards catastrophic misinterpretation of diverse bodily sensations as much more dangerous than they really are, leading to increased avoidance of situations associated with these bodily sensations, may lead to a PA. 39 Another finding that supports cognitive biases underlying susceptibility to panic/agoraphobia is the fact that subjects with PD perceive symptoms as more embarrassing than controls. 40 Furthermore, the more catastrophically a symptom is interpreted, the more intense will the agoraphobic avoidance be. 41 Lower quality of life in patients with PD as compared with healthy controls, as measured by the SF-36 in this study, has been reported previously in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that self‐perceived symptom severity and degree of distress are independent factors of the level of need for health care, suggesting that the routine use of simple questionnaires to assess symptom experience and symptom‐associated distress is needed to improve the quality of postoperative health care. Other reports, however, have suggested that self‐perceived symptoms do not play a significant role in care‐seeking behaviour for the worst attacks (Katerndahl 2000). In addition, perceptions of overall disease severity may not correlate with disease activity measures based on current symptomatology (Kane et al.…”
Section: Discussionmentioning
confidence: 99%